PRIORITY DIRECTIONS OF ENVIRONMENTAL EDUCATION IN THE UNESCO CONCEPT - Fayziyev Muhammad Shukrulloyevich (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
Environmental education has become one of the most important global priorities in the twenty-first century due to climate change, biodiversity loss, environmental degradation, water scarcity, and the unsustainable use of natural resources. International organizations, particularly the UNESCO, have played a leading role in shaping global environmental education policies and strategies. UNESCO considers environmental education not only as a process of teaching ecological knowledge but also as a mechanism for developing environmental responsibility, sustainable lifestyles, and global citizenship. The organization emphasizes interdisciplinary learning, lifelong education, community participation, digital innovation, and sustainability-oriented educational reforms. UNESCO’s environmental education concept is closely connected with the Sustainable Development Goals, especially Goal 4 on quality education and Goal 13 on climate action. The present article analyzes the priority directions of environmental education in UNESCO’s conceptual framework, including sustainable development education, climate literacy, ecological ethics, inclusive participation, technological integration, and environmental culture formation. The study also highlights the significance of environmental education for social stability, economic sustainability, and global ecological security in modern society.